APLIKASI SOFTWARE ENGINEERING QUESTION OTOMATIS MENGGUNAKAN METODE COSINE SIMILARITY BERBASIS ANDROID - Modesta Kase; Oman Adil Karib Dakhi; Satria Aryo Prakoso; Muhammad Farhan Ambiya; Aries Saifudin (CV. Multi Kreasi Media, 2024)
Keyword matching methods are still used by today's question answering software to find answers. A system that automatically searches for appropriate answers to user questions is known as an automatic question answering system. To help and make it easier to answer questions about software engineering, questions can be created. For word processing systems, this application uses the Cosine Similarity approach, which can help us get the necessary information. The information sought by the asker can be found with automatic debriefing by designating the answer with the highest weight as the most appropriate answer. According to specialists and system evaluations, the first response, or the one with the most weight, is the most correct. The original response or the response with the highest weight produced by the system, according to system evaluation, expert assessment, and Kappa testing, is the correct response. The first answer that has the largest weight has the best Kappa value according to test results using Kappa statistics. This value shows that this system is able to compare use cases of questions and responses using the system that has been developed.